MATHEMATICAL MODEL FOR DIRECT EVAPORATIVE SPACE COOLING SYSTEMS (Nigerian Journal of Technology, 2013)
This paper deals with the development of a simple mathematical model for experimental validation of the performance of a small evaporative cooling system in a tropical climate. It also presents the coefficient of convective heat transfer of wide range of temperatures based on existing model. Extensive experiments have been performed during January to February 2013 for a small evaporative cooling system designed for storage of fruits and vegetables. The model considered the thermal properties of the material of the cooling pad and assumed that the cooling pad is a plain porous wall bounded by two convective air at different temperature at the two surfaces. The predicted and experimental value of various cooling efficiency at different range of inlet temperature has been determined. In addition the values of the coefficient of convective heat transfer for a wide range of temperatures is also presented.